Recent experience and performance during a critical in‐flight event. Issue 6 (5th November 2022) - Wiggins, Mark W.; Yuris, Nadya; Molesworth, Brett R. C.
Abstract: The aim of this study was to test, amongst less experienced pilots, the relationship between the recency of flight experience and performance during a critical in‐flight event. It was hypothesised that, in response to an engine failure, recent flight experience would be associated with a superior level of aircraft control, decreased cognitive load, and a successful landing at an alternate destination. Pilots completed a simulated flight during which an engine failure occurred. The weather conditions and proximity to the alternate were designed to enable a power‐off landing. The results revealed a relationship between recent flight experience and landing at the alternate, although no relationship was evident with aircraft control. Objective, rather than subjective levels of cognitive load tended to covary with landing successfully at the alternate. The outcomes provide support for the role of recent flight experience in enabling successful responses to critical in‐flight events, particularly amongst less experienced pilots.